Near-infrared photoactivatable semiconducting polymer nanocomplexes with bispecific metabolism interventions for enhanced cancer immunotherapy. (October 2022) - Yu, Ningyue; Ding, Mengbin; Wang, Fengshuo; Zhou, Jianhui; Shi, Xiangyang; Cai, Rong; Li, Jingchao
Abstract: Cancer metabolic programs play important roles in restricting various anticancer therapies. Although metabolism interventions using inhibitors can provide an alternative way for cancer treatment, the uncontrolled bioactivity and accumulation of inhibitors often lead to limited therapeutic efficacy and off-target side effects. To address these concerns, we herein develop semiconducting polymer nanocomplexes (SPNCN ) that can specifically inhibit autophagy and immunometabolism in tumor microenvironment upon near-infrared (NIR) photoactivation for enhanced cancer immunotherapy. Such SPNCN consist of a semiconducting polymer nanoparticle as the core and singlet oxygen ( 1 O2 )-responsive shell with the encapsulations of chloroquine (CQ) and NLG919 as the autophagy and immunometabolism inhibitor, respectively. SPNCN upon NIR photoactivation generate 1 O2 to exert photodynamic therapy (PDT) for killing tumor cells and inducing immunogenic cell death (ICD), and the produced 1 O2 effectively destroys the 1 O2 -responsive shells to achieve precise release of CQ and NLG919 in the tumor microenvironment. CQ inhibits autophagy to amplify PDT effect and ICD, and NLG919 intervenes immunosuppressive tryptophan (Trp) metabolism, synergistically improving the antitumor immunity. Therefore, SPNCN -mediated enhanced therapy can inhibit the growth of tumors in bilateral melanoma-bearing mouse models. This work offers a smart polymer platform to integrate the bispecific metabolism interventions with cancer therapy in a safe and effective manner. Graphical Abstract: ga1 Highlights: Semiconducting polymer nanocomplexes can achieve near-infrared light-triggered precise release of two metabolism inhibitors in tumor microenvironment. Semiconducting polymer nanocomplexes after photoactivation exert photodynamic therapy and inhibit autophagy and immunometabolism . Semiconducting polymer nanocomplexes lead to amplified photodynamic therapy effect and immunogenic cell death, thus improving the antitumor immunity for treatment of melanoma.